Does botulinum therapy affect the urine microbiome of patients with neurogenic bladder? Metagenomic sequencing results - E. S. Philippova; I. V. Bazhenov; A. V. Zyrianov (Вестник урологии)
Introduction. Reorganization of the urinary microbiome in patients with neurogenic low urinary tract dysfunction (NLUTD) plays an important role in the pathogenesis of urinary tract infections (UTIs). However, we still do not know how the different types of NULTD therapy affect the microbiome.Purpose of the study. Was to assess the influence of botulinum toxin (BoNT) injections on the urinary microbiome.Materials and methods. Urine samples were obtained from 6 persons (4 females and 2 males) with NLUTD before BoNT therapy (200 UI) and 6 weeks after. Standard urine analysis, urine culture and 16S rRNA gene sequencing were performed. a total of 144,562 quality-filtered 16S rDNA sequence reads were processed through an Illumina MiSeq platform.Results. The results of the urine culture correlated with 16S rRNA sequencing results, but the greater number of bacterial taxa were detected. Analysis of the bacterial community in urine samples revealed between 2 and 21 species-level reads per individual. All patients before BoNT demonstrated abnormal urinary microbiome with a predominance of Enterobacteriales. In three cases in females, clinical and urodynamic improvement after botulinum therapy was associated with changing of the microbiome from Enterobacteriaceae to Lactobacillales. In one female and two males, no principal changes had happened.Conclusions. This is the first report comparing in pilot study the urinary microbiome before and after BoNT injections into the bladder wall. The results are restricted by the small number of participants. However, the promising observation about the influence of botulinum toxin therapy on urinary microbiome was obtained.